Predictive Factors for Good Outcome and Mortality After Stent-Retriever Thrombectomy in Patients With Acute Anterior Circulation Stroke - Yoon, Woong; Kim, Seul Kee; Park, Man Seok; Baek, Byung Hyun; Lee, Yun Young (Journal of stroke, 2017)
Predictive factors associated with stent-retriever thrombectomy for patients with acute anterior circulation stroke remain to be elucidated. This study aimed to investigate clinical and procedural factors predictive of good outcome and mortality after stent-retriever thrombectomy in a large cohort of patients with acute anterior circulation stroke. We analyzed clinical and procedural data in 335 patients with acute anterior circulation stroke treated with stent-retriever thrombectomy. A good outcome was defined as a modified Rankin Scale score of 0 to 2 at 3 months. The associations between clinical, imaging, and procedural factors and good outcome and mortality, respectively, were evaluated using logistic regression analysis. Using multivariate analysis, age (odds ratio [OR], 0.965; 95% confidence interval [CI], 0.944-0.986; =0.001), successful revascularization (OR, 4.658; 95% CI, 2.240-9.689; <0.001), parenchymal hemorrhage (OR, 0.150; 95% CI, 0.049-0.460; =0.001), and baseline NIHSS score (OR, 0.908; 95% CI, 0.855-0.965; =0.002) were independent predictors of good outcome. Independent predictors of mortality were age (OR, 1.043; 95% CI, 1.002-1.086; =0.041), successful revascularization (OR, 0.171; 95% CI, 0.079-0.370; <0.001), parenchymal hemorrhage (OR, 2.961; 95% CI, 1.059-8.276; =0.038), and a history of previous stroke/TIA (OR, 3.124; 95% CI, 1.340-7.281; =0.008). Age, revascularization status, and parenchymal hemorrhage are independent predictors of both good outcome and mortality after stent retriever thrombectomy for acute anterior circulation stroke. In addition, NIHSS score on admission is independently associated with good outcome, whereas a history of previous stroke is independently associated with mortality.